The Interaction of Antiviral Drugs with SARS-Cov-2 3CL Protease (Journal of Pharmaceutical Negative Results, 2022)
SARS COV2 is one of the most destructive pandemics the world has faced and led to extreme economic losses. For its clinical therapy,SARS-COV-2 3CL Protease (3CLpro) is considered a target because of its crucial role in replication. Inhibition of this 3CLpro can lead toa decrease in viral load and infection. Different studies used various compounds and tested their inhibiting activity. Among them, flavonoids,serine derivatives, Chalcones, and alpha-keto amides were proven to have inhibitory effects. Many in-vitro tests were done to check thebinding and inhibition abilities of such compounds. In vivo, some studies are done, but more is needed to prove this discovery. As far asresearch is concerned, therapeutic drugs against COVID-19 can be made by using such inhibitors. More in vivo studies and animal modelexperimentation should be done to confirm the findings.